Old and Older Curriculum Standards for History and Archeology - Black, Mary S. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This paper examines the standards and principles recently proposed for teaching both history and archeology. By comparing the goals each discipline has set for good teaching, areas of difference and commonality can be discerned and questions concerning historical thinking and what may be called "archeological" thinking can then be formulated, thus leading to greater understanding not only of subject disciplines, but also of the cognitive functions students must practice to solve problems about the relationship of past and present. Curriculum standards for history and principles for curriculum reform for archeology recently have been promulgated to give greater focus to teaching in these disciplines; both sets of guidelines recommend training in basic research skills (analysis, evaluation, presentation of data), and neither set implies any discrete topics that must be taught. The curriculum standards for history in K-12 as proposed by the National Center for History in the Schools (1996) are focused on important skills for finding meaning in historical materials. These standards are presented as "historical thinking"; that is, the ability to put past events into context and engage in inquiry with the evidence. Guiding principles for the archeology curriculum at the undergraduate level recently have been proposed by the Society for American Archeology. However, no guidelines have been provided for teaching about archeology in K-12 schools. (Contains 2 tables [the guidelines] and 13 references.) (BT)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (New Orleans, LA, April 24-28, 2000).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Standards; Archaeology; Comparative Analysis; Educational Objectives; Elementary Secondary Education; Higher Education; History; National Standards; Social Studies; National History Standards; Reports, Evaluative; Speeches/Meeting Papers